Analysis of IP Valuation on Technology Food Processing as Strategy Business in New Product Development - Syukri Yusuf Nasution; Yovita Isnasari (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
Valuation IP of IDS000001555 analysed the economic impact and to measure the financial benefits of the asset if implemented in a business. This patent is about technology that used to produce of Mangosteen peel nano-tea. This technology is to product nano particle with ball-mill method. This research used qualitative and quantitative methods with description analysis. By using the qualitative method, this research focused on scoring of the IP in a several aspects, while the quantitative method conducted by income approach used the Discounted Cash Flow method. The qualitative method showed the technology IDS000001555 had a high opportunity and low risk value. This patent also has the best marketing strategy by a licensing agreement. However, the quantitative method showed the technology IDS000001555 had 6.1% for royalty rate with value of NPV (Net Present Value) Rp 605,227,434. It was estimated that this patent will generate the turnover of about Rp 617,000,000 for 10 years of useful economic life.Keywords: valuation IP, economic impact, qualitative and quantitative methods, royalty rate, turnover